Answer:
is the answer
Step-by-step explanation:
First we need to substitute X and Y with their respective numbers
![3\cdot \:6+\frac{6}{-4}-\left(-4\right)^2](https://tex.z-dn.net/?f=3%5Ccdot%20%5C%3A6%2B%5Cfrac%7B6%7D%7B-4%7D-%5Cleft%28-4%5Cright%29%5E2)
Then, following PEMDAS, We just need to simplify
![18+\frac{6}{-4} -16](https://tex.z-dn.net/?f=18%2B%5Cfrac%7B6%7D%7B-4%7D%20-16)
![16.5-16=0.5=\frac{1}{2}](https://tex.z-dn.net/?f=16.5-16%3D0.5%3D%5Cfrac%7B1%7D%7B2%7D)
Answer:
Here you go.
Step-by-step explanation:
Hope this helps you!
Answer:
the answer would be -3 since it's below.